2011
DOI: 10.1111/j.1463-1326.2011.01445.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon gene expression in the endocrine pancreas: the role of the transcription factor Pax6 in α‐cell differentiation, glucagon biosynthesis and secretion

Abstract: The glucagon gene is expressed in α-cells of the pancreas, L cells of the intestine and the hypothalamus. The determinants of the α-cell-specific expression of the glucagon gene are not fully characterized, although Arx, Pax6 and Foxa2 are critical for α-cell differentiation and glucagon gene expression; in addition, the absence of the β-cell-specific transcription factors Pdx1, Pax4 and Nkx6.1 may allow for the glucagon gene to be expressed. Pax6, along with cMaf and MafB, binds to the DNA control element G(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Paired box 6 (PAX6) is a highly conserved transcription regulatory factor involved in multiple biological processes, including embryogenesis, cell differentiation, biosynthesis and cell motility (1,2). Accumulating evidence has demonstrated that PAX6 is crucial in the development of the central nervous system (3).…”
Section: Introductionmentioning
confidence: 99%
“…Paired box 6 (PAX6) is a highly conserved transcription regulatory factor involved in multiple biological processes, including embryogenesis, cell differentiation, biosynthesis and cell motility (1,2). Accumulating evidence has demonstrated that PAX6 is crucial in the development of the central nervous system (3).…”
Section: Introductionmentioning
confidence: 99%
“…Here we review aspects of a-cell specification, differentiation, and maturation. For a more detailed review on a-cell physiology and glucagon regulation please see Gromada et al (2007) and Gosmain et al (2011).…”
Section: Islet A-cell Developmentmentioning
confidence: 99%
“…4A) (Gosmain et al 2011). Pax6 mutants lack a cells, and have reduced glucagon expression and MafB expression, another regulator of glucagon expression that is selectively expressed in adult a cells in mice (Artner et al 2006;Nishimura et al 2006Nishimura et al , 2008Gosmain et al 2010).…”
Section: Islet A-cell Developmentmentioning
confidence: 99%
“…The promoter consists of a region comprising the regulatory sequences G1 and G4 while the remaining sequences are part of the enhancer regions. Numerous transcription factors are involved in the control of glucagon expression such as LIM-homeobox transcription factor islet-1 (Isl1), paired box gene 6 (Pax6), musculoaponeurotic fibrosarcoma oncogene homolog (Mafs), forkhead box protein A1 (Foxa1) and forkhead box protein A2 (Foxa2) among others (81,82) . The transcription of the preproglucagon gene results in a peptide of 160 amino acids.…”
Section: Glucagon Synthesismentioning
confidence: 99%